Análogo de GnRH em veículo de liberação lenta para indução de crescimento folicular em fêmeas bovinas em anestro - Gofert, Leandro Francisco (2015)
To test a new follicular growth inducer on the increase of follicular growth, the rate of ovulation and pregnancy in cows submitted to fixed time artificial insemination (FTAI). Was associated with a GnRH analogue (gonadorelin, Fertagyl®, MSD, São Paulo, Brazil) diluted in 20% sodium hyaluronate solution. It was used 27 Nellore cows, lactating, body condition score (BCS) of 2.5 (range 1-5) in anoestrus (fol. <8 mm and absence of corpus luteum). On day 0 all cows received a progesterone device (Primer® - Tecnopec, São Paulo, Brazil) and 2 mg of estradiol benzoate (RIC-BE® - Tecnopec, São Paulo, Brazil). Eight days later were evaluated by ultrasound and divided into 3 groups, balancing groups by follicular condition, that day all animals had their devices removed and received 500 g of sodium Cloprostenol (Ciosin® - MSD, São Paulo, Brazil). In the G100 group was administered intramuscularly the priming solution of growth with 100 μg of gonadorelin. In the G200 was applied to priming solution of growth with 200 μg of gonadorelin. In the control group (CG) was applied 2 mL of saline solution. On day 9 the animals received 1 mg of estradiol benzoate as ovulation inducer. All animals were inseminated on day 10, 54 h after removal of the devices. In day 9 and 10 the animals were evaluated by ultrasound for follicular measurement, on day 19 for corpus luteum ID (ovulation rate) and day 44 for pregnancy diagnosis. Follicular diameter did not differ between groups at D0: 5.2 ± 1.16 mm vs. 5.8 ± 1.45 mm vs. 5.2 ± 1.55 mm; at D8: 7.3 ± 1.83 mm vs. 8.2 ± 1.67 mm vs. 7.4 ± 1.60 mm; in D9: 9.2 ± 1.69 mm vs. 9.6 ± 1.55 mm vs. 9.2 ± 1.18 mm, respectively, for G100, G200 and GC. Follicular growth between day 8 and 9 also did not differ between groups: 1.9 mm vs. 1.4 mm vs. 1.8 mm, for G100, G200 and GC respectively. The cows treated with GnRH, evaluated in the D10, had anticipation of ovulation in relation to GC: 100% vs. 77.8% vs. 0%, respectively, for G100, G200 and GC. The ovulation rate determined by the presence of CL in the D19 did not differ between the groups: 100% vs. 77.8% vs. 77.8% respectively for G100, G200 and GC, the diameters of corpora lutea did not differ, when evaluated in D19: 1.56 ± 0.24 mm vs. 1.68 ± 0.40 vs. 1.51 ± 0.30 mm, respectively, for G100, G200 and GC. The pregnancy rate was higher in GC than those treated: 33.4% vs. 0 vs. 0, respectively for GC, G100 and G200. The data suggest that the association between the GnRH analogue and hyaluronate 20% (at the doses tested) did not increase follicular growth or ovulation rate. Probably this association induced a premature LH surge, leading to early ovulation and harming the pregnancy rates of the treated animals.